The Covid-19 pandemic and the impact on the lives of families with children with autism spectrum disorder (Revista Contexto & Educação, 2023)
The covid-19 pandemic led to a great impact in the lives of families of children with autism. Therefore, this article which aims to investigate the experience of school-age students with ASD, from the perspective of their carers, with changes in the family routine as well as to map which safety measures the families took after the flexibilization of social isolation norms. This study sought to understand the nuances of these routine modifications and which were the necessary adaptations throughout social isolation. The data collected showed that the maintenance of the bond and the routine are essential, as well as the importance of expanding this care to the families.
Keywords: Autism Spectrum Disorder; Pandemic; Perceptions; Children; Carers